Komposisi Tabuh Kreasi Sekar Taji - I Kadek Deo Sandiawan; Hendra Santosa; Ni Putu Hartini (Journal of Music Science, Technology, and Industry, 2022)
Purpose: The creation of a musical piece of musical art creation "Sekar Taji" is to realize the imagination or thoughts of the stylist in a new creative musical work. The stylist got an idea from his own experience to make a creative percussion using the gamelan Gong Kebyar as a medium of expression. Research Method: To achieve Balinese musical works, the stylist uses several methods or stages for the creation process, namely the first with the preparation stage, the exploration stage, the formation stage, the guidance stage and the presentation stage. Results and discussion: The Tabuh Kreasi work "Sekar Taji" uses a kawitan, gendered, bapang and pusher structure by combining musical elements such as dynamics, tempo, melody and rhythm that are combined in such a way as to achieve a karawitan musical work, namely percussion creations. Implication: This work is manifested into a creative percussion through a creative process using existing patterns and patterns of strokes as a means of stimulating creativity in the sector of musical art.